2005
DOI: 10.1080/03008880510030950
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prostate cancer pathology: Current issues and achievements

Abstract: Recent developments in the field of molecular techniques have provided new tools that have led to the discovery of many new promising biomarkers for prostate cancer. These biomarkers may be instrumental in the development of new tests that will have a high specificity for the diagnosis and prognosis of prostate cancer. A biomarker is defined as a molecular test that provides additional information to currently available clinical and pathological tests. Biomarkers should be reproducible (both within and between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
6
0
3
Order By: Relevance
“…Although, nomograms based on pre- and post-operative parameters offer some information about patients’ prognosis, limited knowledge about which CaP is likely to progress, as well as, when it will recur severely impedes individualized selection of therapy and subsequent prediction of outcome [23]. Recent studies have shown that chemokines, cytokines and other proteins that are associated with inflammatory processes may function in promoting tumor invasion and metastasis [24–26]. Furthermore, some of these molecules, such as cyclooxygease-2 have shown prognostic potential for predicting CaP progression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although, nomograms based on pre- and post-operative parameters offer some information about patients’ prognosis, limited knowledge about which CaP is likely to progress, as well as, when it will recur severely impedes individualized selection of therapy and subsequent prediction of outcome [23]. Recent studies have shown that chemokines, cytokines and other proteins that are associated with inflammatory processes may function in promoting tumor invasion and metastasis [24–26]. Furthermore, some of these molecules, such as cyclooxygease-2 have shown prognostic potential for predicting CaP progression [18].…”
Section: Discussionmentioning
confidence: 99%
“…This complicates diagnosis and therapy, because it is not sufficient to detect tumors, but also necessary to distinguish forms of the disease requiring palliative treatment, definitive therapy, or active monitoring, respectively. Moreover, since definitive therapy can be performed by surgery or irradiation and may be supplemented by antiandrogenic therapy and cytotoxic chemotherapy depending on the circumstances of each individual case, criteria for optimal selection of therapy are desirable [2].…”
mentioning
confidence: 99%
“…Other preoperative factors may improve the predictive accuracy for pathologic stage, including neuroendocrine (NE) differentiation, nuclear DNA content, and MVD [36,66] (Table 7). …”
Section: Prognostic Molecular Markers (And Methods)mentioning
confidence: 99%
“…The discovery of new molecular markers that, in a needle biopsy setting, are of prognostic significance is very much the need of the hour (Table 7) [58,66].…”
Section: Other Molecular Markersmentioning
confidence: 99%